Socio-Demographic Characteristics of Acute Myocardial Infarction Patients in Bangladesh - Khan, MMR; Sana, NK; Basak, PM; Sarker, BC; Islam, M Akhtarul; Jahan, KI; Rahman, MK; Rashid, MHO; Sarker, A; Das, CK; et al. (TAJ: Journal of Teachers Association, 2018)
Background: The impacts of socio-demographic characteristics on acute myocardial infarction (AMI) are not well understood and have not yet been studied much more in our country. Acute myocardial infarction is the most common form of coronary heart disease and the single most important cause of premature death worldwide. Objective: The aim of this study was to assess the impacts of the socio-demographic characteristics on AMI patients and to investigate the association between socioeconomic status and its various indicators and the risk of acute myocardial infarction (AMI). This study will help in awareness building in reducing AMI by early detection of socio-demographic variables. Patients and methods: This was a prospective observational study consisted of 325 persons of AMI patients who were aged >20 years. Patients with first time AMI arriving in Coronary Care Unit (CCU) of Rajshahi medical college during the period of 2012-2014, were included. Data were collected through interview. Results: Among the AMI patients, male were more sufferer than female (68.3% vs. 31.7%) and male and female ratio was 2.15:1.0. Highest percentage of education was up to primary level (53.85%). Most of studied subjects (92.0%) monthly income were ≤15000. More than half (59.38%) of the studied population were from rural area, mostly they were Muslim (94.46%) and smokers (50.15%). The mean±SD age of the acute Myocardial infarction patients was 53.75±11.64 years. Mean age of the female patients were a little bit higher than the male patients (female 54.28±11.78 vs. male 53.51±11.63). Highest percentage was in the age group 51-60 years (32%) followed by 41-50 (26.8%) and then age group >60 (23.7%). Among the male patients highest percentage was in the age group 51-60 years (31.1%) followed by 41-50 years (27%) and then age group >60 (24.3%). However, among the female patients, highest percentage were in the age group 51-60 years (34%) followed by 41-50 years (26.2%), and then age group >60 (22.3%). Acute Myocardial infarction patients was more in age group >40 years of age. Interestingly after 60 years of age occurrence of AMI was low in both sexes. Conclusion: Both sex and age influenced AMI. An association was also found among educational level, monthly income, residence area, religion, smoking habit and AMI. TAJ 2016; 29(1): 16-20